Factors Contributing to Receptivity to New Clean Air Law Among Transylvanian Teenagers - Albert-Lőrincz Enikő; Dániel Botond; Foley L. Kristie; Szabó Béla; Paulik Edit; Gáspárik Andrea Ildikó (2019)
In March 2016, a new Clean Air Law was implemented in Romania, which bans smoking in common areas and enclosed public spaces. The aim of study was to assess the perceptions of the new tobacco control law among adolescents in Romania and to understand the role of sociodemographic, behavioral, environmental and personal factors on influencing adolescent perceptions. We conducted a self-administered, cross-sectional survey of 695 7th grade students from 21 localities, 21 schools, and 55 classes. Logistic regression was used to assess the correlates of acceptance of the clean air law. Most of the responders (94.8%) had heard about the new law, and 76.0% of the students agreed with the bans on smoking in closed places. According to the regression analysis the law was eight times more accepted by the non-smokers. It is also important how informed they are concerning the law - more they know, more they accept it.